Preparation, surface functionalization and application of Fe3O4 magnetic nanoparticles - Liu, Shixiang; Yu, Bing; Wang, Song; Shen, Youqing; Cong, Hailin (Advances in colloid and interface science, 2020)
This paper reviews recent developments in the preparation, surface functionalization, and applications of Fe3O4 magnetic nanoparticles. Especially, it includes preparation methods (such as electrodeposition, polyol methods, etc.), organic materials (such as polymers, small molecules, surfactants, biomolecules, etc.) or inorganic materials (such as silica, metals, and metal oxidation/sulfide, functionalized coating of carbon surface, graphene, etc.) and its applications (such as magnetic separation, protein fixation, magnetic catalyst, environmental treatment, medical research, etc.). In the end, some existing challenges and possible future trends in the field were discussed. [Display omitted] •Comprehensive summary of the main aspects of Fe3O4 magnetic nanoparticles related to their preparation and application.•Classification and intrinsic properties of Fe3O4 magnetic nanoparticles were studied.•Perspectives for the future developments of Fe3O4 magnetic nanoparticles were proposed.